Lipoblastoma nose: a rare case report - Patil, Amol A.; Patangrao, Hruchali; Gunasekar, Kalpana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Lipoblastoma is a rare exclusively benign encapsulated tumor arising from embryonic white fat. Tumor occurs primarily in infancy and early childhood. It often presents as painless swelling in extremities and trunk, and rarely develops in head and neck and other sites. We report case of a 15 months old boy with a gradually enlarging, painless swelling over the left side of the dorsum of nose. Computed tomography scan revealed a subdermal soft tissue mass. Treatment remains complete surgical excision. Diagnosis is determined by histopathologic findings. Histologically, lipoblastoma reveals immature adipose cells in varying stages of maturity arranged into lobules separated by septa. No recurrence of tumor has been noted over 6 months of follow-up of this patient.